Potential eutrophication of Sungai Sarawak - Wong, Wei Ping (Universiti Malaysia Sarawak (UNIMAS), 2002)
One major impact human have had on marine ecosystem is eutrophication. Eutrophication is enhanced production of primary producers as a result of excessive input of nutrients into the ccos),.tem. The excessive input of nutrients is mainly from human activity, farming, and development activity. The nutrients such as phosphate and nitrate are believed to be the key for eutwphication. Eutrophication will lead to various problems such as toxic algal bloom, loss of marine food . upply and habitat. This study had been focused on the factors such as initial nutrients loading, pH, dissolved oxygen level and total suspended solid that affect the sorption and release of nutrients (phosphate and nitrate) from sediments to the water column, and on developing an empirical model to predict the potential eutrophication of Sg. Sarawak. This research had identified that under anoxic (Io~ DO) and acidic (low pH) conditions, phosphorus release from sediments was enhanced. A twofold increase of the phosphate release from sediments was demonstrated in this study. However, the data shown very low desorbability of added or adsorbed phosphate due to the formation of chemical (ligand) bonding between phosphate and the adsorption sites and immobilization of phosphate as iqsolublc fcrric phosphate. Even though there was no apparent influence of dissolved oxygen on ni~u: release from the sediments but as pH rose, desorption of nitrate ion increased as the hydroxide ions can easily replace nitrate ions at the sorption sites. This study also shown very little nitrate "i!csoretiun even though nitrate is known to be weakly bound to positive sorption sites in the sediments -throu~h physical bonding and therefore nitrate adsorption reaction is reversible. This may be due to sigQ.i licant fixation had occurred during the spiking stage when nitrate-nitrogen was transformed to ammonium-nitrogen. Ammonium release from sediments increased with pH but decreased with increased dissolved oxygen. Sorption of phosphate increased as pH increased but sorption of nitrate decreased with pH. Enhanced sorption of phosphate and nitrate were observed by increasing the aln<Amt of sediments but the amount adsorbed (mg/g) decreased. This could attribute to the heterogeneity in sediment composition even though the amount of adsorption sites on sediment particles increased in proportion with the amount of sediment. These findings will help the environmental officers or any organization to come up with programs or measures to control and monitor Ule nutrients level in the water column. The empirical models developed in this study may serve as a preliminary tool to assess the nutrients level at any particular time and to minimize pollution of water bodies.